Trends in the management of global economic development in the post-pandemic period - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Чичун, Валентина Андріївна; Чичун, В. А.; Чичун, Валентина Андреевна; Chychun, Valentyna A.; Шупрудько, Наталія Володимирівна; Шупрудько, Н. В.; Шупрудько, Наталия Владимировна; et al. (Faculty of Business Economics and Entrepreneurship, 2021)
This article is devoted to the study of trends in the management of global economic development in the post-pandemic period. The paper developed recommendations for further development of countries in the context of the recurrence of pandemics. With this in mind, the main trends in the development of countries during the pandemic were considered and the impact of quarantine on the economies of various countries was determined. To model the future actions of states, based on studies of the historical preconditions for the development of countries in the post-crisis period, the basic patterns were identified, allowing to predict different scenarios of world economic development.The article introduces a forecasting method of global economic development based on the quadrant of trust and affluence of the population, which allows predicting various options for post-pandemic development according to four possible scenarios. The first option is a rapid V-shaped growth, which is based on the fact that with a sufficient level of public confidence in the government, as soon as the quarantine restrictions expire, the economy will gain momentum. The second one is the long-term U-shaped growth, which is expected to take place in terms of insufficient public confidence in the government, with a population reluctant to invest in economic growth. The third one is the L-shaped development, which does not provide for economic recovery in the short run due to public distrust and the impossibility of business recovery. Finally, the fourth scenario is the worst one: it's the way of development, that occurs in case of impossibility of survival and complete distrust to the government; the population will be forced to organize protests and revolutions, thus making the economy operate even worse. According to the expectations of international regulators, V or U-shaped recovery of the world economy after the COVID-19 pandemic is expected nowadays. Most businessmen believe that post-pandemic development will be U-shaped. To improve the mechanisms of managing the development of world economies, the directions of development are proposed focused not on capitalist, but social goals. The state should occupy an important place in this process acting as a guarantor of efficient allocation of resources and providing social guarantees to the population during possible further cataclysms.

Ця стаття присвячена дослідженню тенденцій управління глобальним економічним розвитком у постпандемічний період. У роботі розроблено рекомендації щодо подальшого розвитку країн в умовах повторення пандемій. З огляду на це, розглянуто основні тенденції розвитку країн під час пандемії та визначено вплив карантину на економіки різних країн. Для моделювання майбутніх дій держав на основі дослідження історичних передумов розвитку країн у посткризовий період визначено основні закономірності, що дозволяють прогнозувати різні сценарії розвитку світової економіки. У статті представлено метод прогнозування глобального економічного розвитку на основі квадранту довіри та достатку населення, що дозволяє прогнозувати різні варіанти постпандемічного розвитку за чотирма можливими сценаріями. Перший варіант – швидке V-подібне зростання, яке базується на тому, що при достатньому рівні довіри населення до влади, як тільки закінчаться карантинні обмеження, економіка набере обертів. Другий — довгострокове U-подібне зростання, яке, як очікується, відбуватиметься в умовах недостатньої довіри населення до влади, з небажанням населення інвестувати в економічне зростання. Третій – це Г-подібний розвиток, який не передбачає відновлення економіки в короткостроковій перспективі через недовіру населення та неможливість відновлення бізнесу. Нарешті, четвертий сценарій є найгіршим: це шлях розвитку, який виникає у разі неможливості виживання та повної недовіри до влади; населення буде змушене організовувати протести та революції, що погіршить роботу економіки. За очікуваннями міжнародних регуляторів, сьогодні очікується V або U-подібне відновлення світової економіки після пандемії COVID-19. Більшість бізнесменів вважають, що розвиток після пандемії буде U-подібним. Для вдосконалення механізмів управління розвитком світових економік пропонуються напрями розвитку, орієнтовані не на капіталістичні, а на соціальні цілі. Важливе місце в цьому процесі має займати держава, виступаючи гарантом ефективного розподілу ресурсів та надання соціальних гарантій населенню під час можливих подальших катаклізмів.
Petrunenko I. Trends in the management of global economic development in the post-pandemic period / I. Petrunenko, V. Chychun, N. Shuprudko, Yu. Kalynichenko, I. Manal // International Review. - No.1-2. - Faculty of Business Economics and Entrepreneurship, 2021. - P. 66-75.
Keywords: COVID-19; economy; postmandemic development; management; COVID-19; економіка; постмандемічний розвиток; менеджмент; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics